1986
DOI: 10.1128/aac.29.5.899
|View full text |Cite
|
Sign up to set email alerts
|

Potentiating effect of pyrimethamine and sulfadoxine against dihydrofolate reductase from pyrimethamine-sensitive and pyrimethamine-resistant Plasmodium chabaudi

Abstract: Dihydrofolate reductase was partially purified from a pyrimethamine-sensitive Plasmodium chabaudi clone and a pyrimethamine-resistant clone derived from it and used in a study of the inhibitory effect of pyrimethamine and sulfadoxine, both alone and in combination. Kinetic analysis of the inhibitory effect of sulfadoxine against the enzyme from pyrimethamine-sensitive and -resistant parasites revealed that the drug inhibited the former enzyme competitively, with an inhibition constant (K1.) of 0.7 + 0.4 mM, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 33 publications
(32 reference statements)
2
6
1
Order By: Relevance
“…These levels of SDX are ≈ 10 5 times higher than those seen to be synergistic with PYR in live parasites, and ≈ 10 2 times higher than the peak level of free SDX (25 μM) attained during Fansidar treatment (Watkins et al ., 1997). This indicates that the synergy that we observed in vivo is not influenced significantly by SDX potentiating the inhibition of DHFR by PYR and is consistent with earlier studies on partially purified enzymes from P. chabaudi (Sirawaraporn and Yuthavong, 1986), in which it was also concluded that the in vivo effect of this antifolate drug combination was much more potent than its effect on DHFR activity. As sulpha drugs are known to give rise to sulpha‐pterin adducts when they compete with pABA on DHPS, it has also been suggested that these, rather than the parent drug, might interact with DHFR (Chulay et al ., 1984).…”
Section: Resultssupporting
confidence: 92%
“…These levels of SDX are ≈ 10 5 times higher than those seen to be synergistic with PYR in live parasites, and ≈ 10 2 times higher than the peak level of free SDX (25 μM) attained during Fansidar treatment (Watkins et al ., 1997). This indicates that the synergy that we observed in vivo is not influenced significantly by SDX potentiating the inhibition of DHFR by PYR and is consistent with earlier studies on partially purified enzymes from P. chabaudi (Sirawaraporn and Yuthavong, 1986), in which it was also concluded that the in vivo effect of this antifolate drug combination was much more potent than its effect on DHFR activity. As sulpha drugs are known to give rise to sulpha‐pterin adducts when they compete with pABA on DHPS, it has also been suggested that these, rather than the parent drug, might interact with DHFR (Chulay et al ., 1984).…”
Section: Resultssupporting
confidence: 92%
“…The selection pattern observed in this area was in keeping with the hypothesis of simultaneous and synergistic inhibition on DHFR by PM and SD 40,41 and supports the proposed model for PM/SD resistance development in Africa. 16 This model has since been criticized 42 and more arguments for and against it put forward.…”
Section: Discussionsupporting
confidence: 85%
“…The ability of this folate salvage pathway and of small amounts of p-ABA to overcome the inhibitory effects of the sulfonamides in vitro (Maier and Riley, 1942;Thurston, 1954) complicated the interpretation of in vitro studies of P. falciparum resistance to sulfonamide drugs and led some to propose that it was the dihydropterin-sulfonamide adducts inhibiting DHFR, rather than a direct sulfonamide inhibitory action on DHPS (Sirawaraporn and Yuthavong, 1986). Studies in E. coli demonstrated that the dihydropterin-sulfonamide products formed do not significantly contribute to the inhibitory action of the sulfonamides (Roland et al, 1979).…”
Section: Folate Effect and In Vitro Sulfonamidementioning
confidence: 99%
“…DHPS mutations and resultant in vivo sulfonamide resistance, particularly with regard to mutations at codons 436 and 613 (Sirawaraporn and Yuthavong, 1986;Sims et al, 1998Sims et al, , 1999Watkins et al, 1999). As with DHFR, recombinant P. falciparum DHPS was incorporated into E. coli for MECHANISMS OF RESISTANCE OF MALARIA PARASITES TO ANTIFOLATES enzyme kinetics studies (Sirawaraporn et al, 1997a;Triglia et al, 1997).…”
Section: Enzyme Kinetics Studies On Dihydropteroate Synthasementioning
confidence: 99%